THE SIGNIFICANCE OF TRANSIT-ORIENTED DEVELOPMENT (TOD) TOWARDS THE ENHANCEMENT OF PUBLIC TRANSPORTATION RIDERSHIP - Sukereman, Anis Syazwani; Noor Saidi, Sarah Yasmin; Sulaiman, Muhammad Azwan; Azmi, Nurul Afiqah; Zainol, Nurul Nadiah (PLANNING MALAYSIA, 2024)
Transit-oriented development (TOD) emerges as a strategic urban planning approach that aims to create well-connected, pedestrian-friendly communities centred around transit nodes. Despite the increasing use of public transportation, many people still rely on single-occupancy vehicles. Several TOD guidelines have been developed to enhance its implementation in Malaysia; however, the current policy context on housing and TOD practices does not adequately reflect the reality that public transport is the preferred mode of transportation for many people. Thus, this study aims to identify the most significant attributes of TOD that can improve public transportation (PT) ridership. Primary data was gathered from 284 respondents using a self-administered questionnaire distributed through simple random sampling. The chi-square test was used to determine the significant relationship between TOD and PT ridership. The findings indicated that eleven TOD attributes and eleven PT ridership attributes had a significant relationship, whilst the remaining relationships were considered null. More than half of the findings were significant, indicating that both TOD and PT ridership were related. In conclusion, a well-designed transit-oriented community can attract and retain public transportation users, making it a catalyst for creating transit-friendly environments.